2010
DOI: 10.4061/2010/781321
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Bracket Manufacturing Tolerances and Dimensional Differences between Select Self-Ligating Brackets

Abstract: In all manufacturing processes there are tolerances; however, orthodontic bracket manufacturers seldom state the slot dimensional tolerances. This experiment develops a novel method of analyzing slot profile dimensions using photographs of the slot. Five points are selected along each wall, and lines are fitted to define a trapezoidal slot shape. This investigation measures slot height at the slot's top and bottom, angles between walls, slot taper, and the linearity of each wall. Slot dimensions for 30 upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
(9 reference statements)
1
17
0
5
Order By: Relevance
“…Major et al 7 reported the Speed brackets to be slightly undersized at the base 0.556 mm (0.0219 inches) with ''pronounced rounding'' and ''large fillets'' where the base meets the wall and slight convergence. Such bases-to-wall issues were also present throughout this sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major et al 7 reported the Speed brackets to be slightly undersized at the base 0.556 mm (0.0219 inches) with ''pronounced rounding'' and ''large fillets'' where the base meets the wall and slight convergence. Such bases-to-wall issues were also present throughout this sample.…”
Section: Discussionmentioning
confidence: 99%
“…Major et al 7 measured 30 upper right central 0.022-inch stainless steel self-ligating brackets from three manufacturers. They reported slot heights from 2% smaller to 3% over the nominal size.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding slot dimensions, Bhalla et al 6 reported that 0.022-inch InOvation-C (Dentsply, York, Penn), Clarity-SL (3M Unitek) brackets had slot tops that were wider than the given value by 11.4% and 9.5%, respectively, and that the bracket slots diverged. According to Major et al, 5 In-Ovation metal brackets (Dentsply), and Damon metal brackets (Ormco) were oversized, and InOvation bracket (Dentsply), slots were divergent, whereas Damon bracket slots (Ormco) were nearly parallel. Moreover, Cash et al, 4 in their study of conventional and self-ligating brackets, reported that all brackets were larger than stated by the manufacturer, with an error range of 5% to 24%.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 As the slot-archwire difference is a major contributor to torsional play, the authors aimed to measure the actual slot sizes and wire dimensions and thus accurately quantify the theoretical torsional play in ceramic self-ligation brackets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation